Using WINROP as an Adjuvant Screening Tool for Retinopathy of Prematurity in Southern Taiwan - Ko, Chia-Hung; Kuo, Hsi-Kung; Chen, Chih-Cheng; Chen, Feng-Shun; Chen, Yi-Hao; Huang, Hsin-Chun; Fang, Po-Chiung; Chung, Mei-Yung (American Journal of Perinatology, 2015)
Objective To study the efficacy of the WINROP (https://winrop.com) algorithm in Taiwan, a middle income, moderately developed country in Asia.Study Design We enrolled all preterm infants born with a gestational age less than 32+0 weeks from September 2008 to August 2010. The results of serial retinopathy of prematurity examinations according to the screening guidelines in our hospital were recorded. Weekly body weight was also recorded for the WINROP algorithm. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated.Results Overall, 148 infants were included. Seventeen infants (11.5%) received treatment for retinopathy of prematurity. But, six infants (35.3%) were missed when severe retinopathy of prematurity was predicted with WINROP algorithm. The sensitivity is only 64.7%. However, when focusing on the preterm infants with a birth weight < 1,000 g or gestational age < 28 weeks, it could predict the need for treatment up to 13 weeks in advance.Conclusion The WINROP algorithm is a very effective noninvasive screening tool for retinopathy of prematurity, especially in preterm infants with a birth weight  < 1,000 g or a gestational age < 28 weeks. However, the overall sensitivity in this report from Taiwan was not as high as that reported in highly developed countries.
Keywords: retinopathy of prematurity; WINROP; prematurity; screening tool